Vulnerable Viterbo. Ancient city form and contemporary pressures - Errigo, Maurizio Francesco; Mrak, Iva (TeMA - Journal of Land Use, Mobility and Environment, 2025)
In Italy the problem of climate change is a question of study that is unfortunately quite recent, more or less since 2015 we have started to understand that this problem exists but it often remains only in administrative theory. The context of the study is emblematic because it is defined by the city of Viterbo in which the system of urban planning rules belongs to a vision, to an idea of the city developed between the 1950s and 1960s and culminated in the approval of the PRG “Smargiassi-Salcini” of 1956 which then merged into the General Variation of 1979, the last unitary instrument of control of the city. Since the 1980s, the city has escaped any holistic vision, avoided the urban planning approach and governance, and pursued its own development outside the master plan rules, favoring the partial variants. The National Recovery and Resilience Programme, presented and hoped for by many as a policy to control territorial imbalances, has not succeeded in this undertaking and has actually contributed to widening the gap between what falls within the domains of the urban planning discipline and what is instead delegated to mere urban or even architectural design.